PENGARUH PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII MTSN OLAK KEMANG KOTA JAMBI - Kiki Putriyani; Aisyah Aisyah; Hasan Basri Said (Universitas Batanghari Jambi, 2018)
Abstract: Teachers are more active in teaching and learning process, while the students only receive the material, question and answer and record so that learning math is very boring for students. To help students to be more active, teachers make various changes or new things in teaching mathematics, one of them by using Contextual Teaching and Learning (CTL) approach. This research includes true experimental research with Pretest-Postest Control Group Design design. Population in this research is all students of class VII MTsN Olak Kemang City Jambi academic year 2017/2018. Sampling using random sampling technique and samples of research are class VII B (experiment) and VII C (control). This study aims to determine whether there is a significant effect of Contextual Teaching and Learning (CTL) approach to the ability to understand the mathematical concepts of students on the subject of the Set. Data collection is done by doing pretest and posttest which each consist of 7 problem. From the result of data analysis done on the difference of pretest-posttest average in two samples obtained titung for the comprehension ability of mathematical concept 4.93 and ttabel is 1.66. At the real level α is 0.05. From the calculation results show that t count is greater than ttable, then H0 is rejected and HI accepted. Based on the final result, it can be concluded that there is a difference of students' understanding of mathematical concept between the experimental class and the control class. Thus, it was concluded that the Contextual Teaching and Learning (CTL) approach significantly influenced the students' understanding of mathematical concepts.Keywords: Influence, Contextual Teaching and Learning (CTL), and Ability to Understand Mathematical Concepts.